PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - Andhi Sukma Hanafi; Chairil Almy; M Tirtana Siregar (Politeknik APP Jakarta, 2018)
Leadership style is a style used by a leader to lead the organization by using existing resources within the organization to achieve organizational goals. Human resources are one of the resources that exist within the organization that can be utilized leader for the achievement of organizational goals. Employees are human resources that can be utilized by a leader in achieving organizational goals. It is important for a leader to be able to use an appropriate leadership style with the organization, in an effort to improve employee work motivation, which affects the performance of employees who support the achievement of organizational goals. In this study will be discussed about the performance of employees who are influenced by the style of leadership and work motivation. The results showed that employee performance is influenced by the level of work motivation and leadership style. In addition, the appropriate style of leader will affect the level of employee motivation, so it can significantly improve the performance of employees within an organization.